Non-cognitive skills and the gender disparities in test scores and teacher assessments: Evidence from primary school - Christopher Cornwell; David B. Mustard; Jessica Van Parys (Institute for the Study of Labor (IZA), 2011)
We extend the analysis of early-emerging gender differences in academic achievement to include both (objective) test scores and (subjective) teacher assessments. Using data from the 1998-99 ECLS-K cohort, we show that the grades awarded by teachers are not aligned with test scores, with the disparities in grading exceeding those in testing outcomes and uniformly favoring girls, and that the misalignment of grades and test scores can be linked to gender differences in non-cognitive development. Girls in every racial category outperform boys on reading tests and the differences are statistically significant in every case except for black fifth-graders. Boys score at least as well on math and science tests as girls, with the strongest evidence of a gender gap appearing among whites. However, boys in all racial categories across all subject areas are not represented in grade distributions where their test scores would predict. Even those boys who perform equally as well as girls on reading, math and science tests are nevertheless graded less favorably by their teachers, but this less favorable treatment essentially vanishes when non-cognitive skills are taken into account. White boys who perform on par with white girls on these subject-area tests and exhibit the same non-cognitive skill level are graded similarly. For some specifications there is evidence of a grade bonus for white boys with test scores and behavior like their girl counterparts. While the evidence is a little weaker for blacks and Hispanics, the message is essentially the same.
urn:nbn:de:101:1-201110102225
Keywords: I21; I24; 330; gender differences; test scores; grades; educational attainment; Bildungsniveau; Kognition; Kinder; Geschlecht; Ethnische Gruppe; Personalbeurteilung; USA